REPRESENTASI CITRA POLISI DALAM FILM KAU ADALAH AKU YANG LAIN - Kurnia, Indang; Rimayanti, Nita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Police of the Republic of Indonesia is a government institution engaged in the field of state security and is tasked to provide services to the community, provide security and serve the community well. it is a form of the image of the Police given to the public. Similarly, this film aims to know the meaning of denotation, connotations and myths in the film You are the Other me and also to know how the representation of the image of the police in movie You are the other me. This research uses qualitative research method with semiotics analysis approach Roland Barthes. Subjects in this research use the scenes that are in the movie You are other me. This study uses data collection techniques through scene observation, documentation and literature study to achieve the validity of data in this study, researchers used the technique Triangulation The results showed that there are three meanings in semiotics Roland Barthes, found the meaning of denotation of police image depicted in the movie you are the other me is the attitude done by the Police in the life of the community, the meaning of the image connotation Police in this film is the nature that is contained within the self The police are shown to the public in the face of a problem and solving the problem. the meaning of the myth in this movie is the attitude or characteristic of a Police when dealing with the people who make the image on the Police become positive. Keywords : Representation, Film, Semiotics and Police